Intracellular pH and the stimulus-secretion coupling in insulin-producing RINm5F cells. - Juntti-Berggren, L; Rorsman, P; Siffert, W; Berggren, P (1992)
The regulation of intracellular pH (pHi) and its role in the insulin-secretory process were evaluated, by using the clonal insulin-secreting cell line RINm5F. Glyceraldehyde, lactate and dihydroxyacetone decreased pHi, but only the first two released insulin. In the presence of extracellular Na+ the cells counteracted the acidification. Blocking the Na+/H+ exchange in acidic cells resulted in a drastic further lowering of pHi, an effect not obtained under basal conditions. Whereas glyceraldehyde depolarized the cells, lactate was without effect. Dihydroxyacetone hyperpolarized the cells in the presence of extracellular Na+, but this effect disappeared when Na+ was excluded from the medium. Stimulation with glyceraldehyde resulted in increased free cytoplasmic Ca2+ concentration ([Ca2+]i). Dihydroxyacetone and lactate had no effect on [Ca2+]i in the presence of Na+, but lactate induced a decrease in [Ca2+]i in Na(+)-deficient medium. In RINm5F cells the activity of the Na+/H+ antiport could not be augmented by activation of protein kinase C (PKC). Hence, in insulin-secreting cells a PKC-insensitive Na+/H+ antiport is the major mechanism restoring a decrease in pHi. Acidification itself does not affect membrane potential, but may directly interact with the mechanisms regulating exocytosis.